Judicial interpretation by the United States courts of the acts of Congress relating to the tariff - Carr, Wm. Wilkins (William Wilkins), 1853- (T. & J.W. Johnson & Co., 1894)
Summaries of legal principles adopted by the courts when interpreting acts of Congress relating to customs revenue.